Unlimited.nl. - Onstwedder, Wineke; van Duyn, Edna (Amsterdam : De Appel Foundation Amsterdam, 1998)
Davids, Yael ; Scha, Arthur Elsenaar & Remko ; Fontune, Yvonne ; Guldenaar, Barbara ; Hagen, Dianne ; Katzir, Ram ; Killaars, Fransje ; Langa, Moshekwa ; Langenberg, Sjaak ; Nollen, Arno ; Oudenampsen, Elka ; De Reus, Paul ; Van Soest, Machiel ; Tan, Fiona ; Wergius, Pia
biografie
Unlimited.nl., De Appel Foundation, Amsterdam, 23 januari - 22 maart 1998
Nederlands
boek
Keywords: Nederland